THU0538 Patients with chronic low back painoriented to functional restoration program are younger, with higher smoking and longer sick leave: a cross- sectional study of 166 patients. (12th June 2018) - Assadourian, M.; Bailly, F.; Letellier, P.; Ascione, S.; Le Ralle, M.; Potel, A.; Morardet, L.; Foltz, V.; Dupeyron, A.; Ibrahim, N.; Griffoul-Espiltalier, I.; Duplan, B.; et al.
Abstract : Background: Functional Restoration Programs (FRP) are multi-disciplinary programs that have demonstrated effectiveness to promote functional status and return to work in patients with chronic low back pain (cLBP) 1; 2; 3 and moderate or high disability. Objectives: To explore the characteristics of cLBP patients oriented or not towards a FRP. Methods: This was an observational cross-sectional, multi-centric study in France in 2017. Consecutive patients with cLBP (>6 weeks) with or without radiculalgia, aged 18–66 years and visiting the rheumatologist for cLBP were included. Patient and disease characteristics were collected. Patients oriented or not towards a FRP were compared in particular for demographic characteristics, duration of sick leave over the past 12 months, smoking, ongoing aerobic physical activity (patient-reported as <or at least 30 min sessions twice a week), anxiety or depression (Hospital Anxiety and Depression Scale≥11), disability (Oswestry >40%) and kinesiophobia (Tampa Kinesiophobia Scale≥40). Results: In all, 166 patients were analysed: median age 48 years, median cLBP duration 5 years, and 100 (60%) were females. Overall, 62 (37 %) were proposed for a FRP. Patients oriented towards a FRP, versus not, were more frequently male (50% vs 44%, p=0.04), younger (median 46 vs 52 years, p=0.02), and had lower pain levels (median 6 vs 7 of 0–10 numeric scale, p=0.006). They had longer sick leave (mean 18 vs 10 weeks/year, p=0.006), were more frequently smokers (33% vs 23%, p=0.02), had similar pain duration (60 month vs 72, p=0.32), functional disabilities (39% vs 49%, p=0.22), kinesiophobia (62% vs 55%, p=0.65), anxiety (52% vs 55%, p=0.60) and depression score (40% vs 35%, p=0.54), but less physical activity practice (38% vs 54%, p=0.04). Conclusions: Patients oriented towards a FRP were younger and more often males, with higher smoking and longer sick leave. It appears that kinesiophobia, functional status and duration of low back pain didn't influence the orientation toward a FRP. More comprehensive assessments of patients with cLBP are needed; multifactorial questionnaires such as StartBack or BP2 may be useful to orient patients towards FRPs. References: [1] Poulain C, et al. Eur Spine J2010Jul;19(7):1153–61. [2] Véron O, et al. Ann Readapt Med Phys2008;51(8):642–9. [3] Roche-Leboucher, et al. Spine2011Dec 15;36(26):2235–42. Disclosure of Interest: None declared